Blind image watermarking scheme based on lowest energy contourlet transform coefficient and modified arnold cat/ikeda maps - Jinan N. Shehab; Hussein A. Abdulkadhim; Yousif Allbadi (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The widespread of global internet has led to the need for developing new methods of protecting multimedia information from exploitation, alteration or forgery, illegal distribution, and manipulation. An attacker is quickly and illegally distributing or changing multimedia information by using various means of computer technology. For detecting this manipulation, this paper suggests blind watermark image inside a host image for observing in the receiver. If the watermark image was retrieved, then the host image was not attacked or manipulated. While if not retrieved, in this case, the image was attacked. The proposed method is depending on a decomposition of the host image using lowest energy sub-bands of Contourlet transform (4-levels), with scrambling by Ikeda map of the watermark image, and selecting new positions by modified Arnold Cat map. This will produce more security and safety, as well as provide more difficulty or prevent hacking. The obtained results confirm the robustness against attacks and more effectiveness of the presented scheme compared with the other similar works. Also, using lowest energy sub-bands will expand area of embedding and this part will be considered in the future works with the color images.